2016
DOI: 10.3892/ijmm.2016.2518
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-214 acts as a potential oncogene in breast cancer by targeting the PTEN-PI3K/Akt signaling pathway

Abstract: Abstract. Breast cancer ranks as the leading cause of cancerrelated mortality in females worldwide. It has been proven that microRNAs (miRNAs or miRs), a type of non-coding RNA, are involved in tumorigenesis. An increasing number of studies has confirmed the critical role of miR-214 in certain types of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…30 A previous study indicated that PTEN was not only a tumor suppressor in the progression of cancers but also a negative regulator of the PI3K/ AKT signaling pathway. 31 It has been reported that as an extremely significant cancer-promoting pathway, the activation of the PI3K/ AKT signaling pathway blocks cellular apoptosis and accelerates cell proliferation by the activation of PTEN or the upregulation of various growth factor receptors including epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor (HER2). 32 GSK3 is regarded as a significant component of diverse signaling pathways involved in the regulation of protein synthesis, cell proliferation, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…30 A previous study indicated that PTEN was not only a tumor suppressor in the progression of cancers but also a negative regulator of the PI3K/ AKT signaling pathway. 31 It has been reported that as an extremely significant cancer-promoting pathway, the activation of the PI3K/ AKT signaling pathway blocks cellular apoptosis and accelerates cell proliferation by the activation of PTEN or the upregulation of various growth factor receptors including epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor (HER2). 32 GSK3 is regarded as a significant component of diverse signaling pathways involved in the regulation of protein synthesis, cell proliferation, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐184 as a putative mammary tumor suppressor performs a central function in inhibiting the proliferation and self‐renewal of TNBC through interaction with Akt2, TSC‐2, PRAS40, and the negative control of the PI3K/Akt/mTOR complex (mTORC)‐1 (Phua et al, ). As an oncomiR, miR‐214 reduces PTEN expression straightly targeting PTEN 3′‐UTR in breast tumor cells (Schwarzenbach, Milde‐Langosch, Steinbach, Muller, & Pantel, ; Wang, Li et al, ). As a result of PTEN downregulation, miR‐214 stimulates cell viability and elevates the improvement of breast tumor via the positive regulation of PI3K/Akt signaling (Wang, Li et al, ).…”
Section: Crosstalk Between Various Signaling Pathways and Mirnas In Bmentioning
confidence: 99%
“…As an oncomiR, miR‐214 reduces PTEN expression straightly targeting PTEN 3′‐UTR in breast tumor cells (Schwarzenbach, Milde‐Langosch, Steinbach, Muller, & Pantel, ; Wang, Li et al, ). As a result of PTEN downregulation, miR‐214 stimulates cell viability and elevates the improvement of breast tumor via the positive regulation of PI3K/Akt signaling (Wang, Li et al, ). MiR‐100 has been emerged to target various proteins of IGF/mTOR signaling in different tumors (Gebeshuber & Martinez, ; Zhang, Zhao et al, ).…”
Section: Crosstalk Between Various Signaling Pathways and Mirnas In Bmentioning
confidence: 99%
“…Breast cancer is the leading cause of cancer-associated mortality among females, and is responsible for 23% of the total cases of cancer and 14% of cancer-associated mortalities globally (1)(2)(3). Multiple chemokines are secreted by cancer cells, and the host cannot regulate this process autonomously (4,5).…”
Section: Introductionmentioning
confidence: 99%